2017
DOI: 10.2147/ijn.s145012
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide-developed silk fibroin nanoplatform for smart colon cancer therapy

Abstract: Purpose To deliver insoluble natural compounds into colon cancer cells in a controlled fashion. Materials and methods Curcumin (CM)–silk fibroin (SF) nanoparticles (NPs) were prepared by solution-enhanced dispersion by supercritical CO 2 (SEDS) (20 MPa pressure, 1:2 CM:SF ratio, 1% concentration), and their physicochemical properties, intracellular uptake efficiency, in vitro anticancer effect, toxicity, and mechanisms were evaluated and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“… 40 In vivo pharmacokinetic study showed the biphasic elimination behaviors of the 5-FU-loaded NCs. 41 , 42 The fact that the drug-loaded NCs follow a biphasic elimination pattern is consistent with data suggesting that a large proportion of the encapsulated 5-FU is lost from the NCs following administration. The second phase of elimination may be due to a fraction of the 5-FU that remains more tightly associated with the inner core of the NCs.…”
Section: Discussionsupporting
confidence: 85%
“… 40 In vivo pharmacokinetic study showed the biphasic elimination behaviors of the 5-FU-loaded NCs. 41 , 42 The fact that the drug-loaded NCs follow a biphasic elimination pattern is consistent with data suggesting that a large proportion of the encapsulated 5-FU is lost from the NCs following administration. The second phase of elimination may be due to a fraction of the 5-FU that remains more tightly associated with the inner core of the NCs.…”
Section: Discussionsupporting
confidence: 85%
“…Also, curcumin silk fibroin (CUR-SF) nanoparticles provided a more stable delivery to colon cancer cells and produced a strong anticancer effect than it's freeform in HCT116 cells. This study concludes controlled release of CUR-SF can able to improve a curcumin cellular uptake into cancer cells and reduce the cytotoxicity to normal cells (Xie et al, 2017).…”
Section: Nanoparticlesmentioning
confidence: 66%
“…Exhibited strong wound healing and long blood circulation, suppression of tumor growth, higher growth inhibition in cancer cells than free curcumin, and increased the cellular uptake and better anticancer activity Li et al, 2012;Anitha et al, 2014;Chaurasia et al, 2016;Xie et al, 2017;Moballegh Nasery et al, 2020…”
Section: Wound Healing and Colorectal Cancermentioning
confidence: 99%
“…However, unlike other main SCF techniques, the nozzle of SEDS presents a coaxial design with a mixing length, in order to produce super-saturated solutions, facilitate precipitation of the solid in the form of small particles with high dispersion. 32 In addition, we added an ultrasonic system to enhance the effect of SEDS technology which can obtain further smaller particles and make the drug more evenly loaded into the carriers.…”
Section: Introductionmentioning
confidence: 99%